2016
DOI: 10.2175/106143016x14609975747441
|View full text |Cite|
|
Sign up to set email alerts
|

Pyrolysis of Dried Wastewater Biosolids Can Be Energy Positive

Abstract: Pyrolysis is a thermal process that converts biosolids into biochar (a soil amendment), py-oil and py-gas, which can be energy sources. The objectives of this research were to determine the product yield of dried biosolids during pyrolysis and the energy requirements of pyrolysis. Bench-scale experiments revealed that temperature increases up to 500 °C substantially decreased the fraction of biochar and increased the fraction of py-oil. Py-gas yield increased above 500 °C. The energy required for pyrolysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 38 publications
0
49
0
Order By: Relevance
“…Till date, there exists one study where energy balance of pyrolysis process for the production of biochar from biosolids has been performed. The study confirmed that pyrolysis of biosolids can be energy positive if energy required for pyrolysis can be sufficed by py‐gas and py‐oil . However, the study is limited to dry biosolids (~5% moisture content).…”
Section: Introductionmentioning
confidence: 57%
“…Till date, there exists one study where energy balance of pyrolysis process for the production of biochar from biosolids has been performed. The study confirmed that pyrolysis of biosolids can be energy positive if energy required for pyrolysis can be sufficed by py‐gas and py‐oil . However, the study is limited to dry biosolids (~5% moisture content).…”
Section: Introductionmentioning
confidence: 57%
“…contest the claim that pyrolysis of heat-dried biosolids can be energy positive (Rollinson & Oladejo, 2019a). We write here to add clarity to this topic, as well as to address specific points raised on our paper (McNamara, Koch, Liu, & Zitomer, 2016) in recent correspondence (Rollinson & Oladejo, 2019b).…”
Section: Patrick Mcnamara Daniel Zitomer Zhongzhe Liumentioning
confidence: 92%
“…Primary and waste activated sludge volumes produced from municipal water reclamation processes are increasing due to population increase and more strict effluent requirements (Agrafioti et al, 2013;Bravo et al, 2017). Conventional solids management including landfilling and biosolids land application for agriculture are employed (Agrafioti et al, 2013;McNamara et al, 2016). However, there are health and environmental concerns related to these approaches due to pathogens, micropollutants, and excess nutrients in the environment as well as a desire for energy and resource recovery from wastewater solids (Bridle and Skrypski-Mantele, 2004;Tsai et al, 2009;Hamidi et al, 2017;Khazaei et al, 2017Khazaei et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrolysis is one thermochemical technology that converts wastewater solids to biochar, pyrolysis gas (py-gas), and pyrolysis liquid. In pyrolysis, sludges or solids are heated in the absence of oxygen to temperatures >400 • C (McNamara et al, 2016;Liu et al, 2017Liu et al, , 2018. Biochar is a solid product similar to charcoal that can be used as a beneficial soil amendment because of its high capacity to hold moisture and nutrients for plants (Laird et al, 2009;McNamara et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation